Bioprospecting of Potential Probiotic Lactic Acid Bacteria from the Gut of Native Chickens (Gallus domesticus) in the Antang Landfill Ecosystem - Khaerunnisa, Khaerunnisa; Dwyana, Zaraswati; Sulfahri, Sulfahri (Indonesian Journal of Ecology and Conservation, 2024)
The use of antibiotics as antibiotic growth promoters (AGPs) in the poultry industry has raised concerns due to increasing bacterial resistance and the potential presence of antibiotic residues in animal products. Consequently, probiotics have been widely explored as a safer alternative to improve livestock health and productivity. Lactic acid bacteria (LAB) are among the most commonly used probiotic microorganisms because they can maintain intestinal microbial balance and produce antimicrobial compounds that inhibit pathogenic bacteria. However, information regarding LAB derived from the intestines of native chickens inhabiting unique ecosystems such as landfill sites remains limited. This study aimed to bioprospect potential probiotic LAB from the intestines of native chickens (Gallus domesticus) living in the Antang landfill ecosystem and evaluate their application in broiler chickens. LAB were isolated using MRSA medium enriched with CaCO₃, followed by morphological identification, Gram staining, and probiotic characterization through acid tolerance, bile salt tolerance, and antagonistic activity tests against Escherichia coli and Salmonella typhi. Eight LAB isolates were obtained, of which five showed promising probiotic potential. The best isolate demonstrated strong antibacterial activity and improved body weight gain and feed efficiency in broiler chickens